Association between serum copper levels and risk of cardiovascular disease: a nested case-control study in the PREDIMED trial - Muñoz-Bravo, Carlos; Olmedo, Pablo; Gil, Fernando; Ruiz-Canela, Miguel; Martínez-González, Miguel A.; Martínez, María Ángeles; Babio, Nancy; Fitó, Montserrat; Del Val García, José Luis; Corella, Dolores; Sorlí, José V.; Ros, Emilio; et al. (Elsevier, 2023)
Background and aim: Certain trace elements have been associated with increased cardiovascular risk. The aim of this study was to evaluate the association between serum copper (SeCu) levels and the risk of a first event of cardiovascular disease (CVD) in a population of older adults with high cardiovascular risk. Methods and results: We conducted a case-control study nested within the PREDIMED trial. During a median follow-up of 4.8 years, a total of 207 incident cases diagnosed with CVD were matched for sex, age, and intervention group with 436 controls. Personal interviews, reviews of medical records, and validated questionnaires were used to assess known CVD risk factors. Biological serum samples were collected annually. Inductively coupled plasma mass spectrometry analysis was used to determine SeCu levels. Adjusted odds ratios were calculated using multivariate conditional logistic regression models. All participants had SeCu levels within the reference values, 750 mg/L to 1450 mg/L. Among men, but not among women, the mean SeCu concentration was higher in cases 1014.1 mg/L than in controls 959.3 mg/L; (p Z 0.004). In men, the multivariable-adjusted odds ratio for CVD was 2.36 (95% CI 1.07e5.20 for the comparison of the highest vs. the lowest quartile; p for trend Z 0.02), in women, it was 0.43 (95% CI 0.11 e1.70; p for trend Z 0.165). Conclusion: In older Spanish men with high cardiovascular risk, a significant association was observed between high SeCu levels, but still within the reference values, and an increased risk of a first event of CVD. Our findings suggest a sex difference in CVD risk and SeCu levels. To confirm this relationship and to analyze the differences observed between men and women, further studies are needed.
Keywords: Sistema cardiovascular - Enfermedades; Serum copper; Trace elements; Cardiovascular diseases; Infarction; Stroke; PREDIMED